The Systems for Generalized of Vector Quasiequilibrium Problems and Its Applications - Le, Huynh My Van (H. : ĐHQGHN, 2017)
In this paper, we study the systems of generalized quasiequilibrium problems which includes as special cases the generalized vector quasi-equilibrium problems, vector quasiequilibrium problems, and establish the existence results for its solutions by using fixed-point theorem. Moreover, we also discuss the closedness of the solution sets of systems of generalized quasiequilibrium problems. As special cases, we also derive the existence results for vector quasiequilibrium problems and vector quasivariational inequality problems. Our results are new and improve recent existing ones in the literature.